The photocycle of orange carotenoid protein conceals distinct intermediates and asynchronous changes in the carotenoid and protein components. Issue 1 (December 2017) - Maksimov, E.; Sluchanko, N.; Slonimskiy, Y.; Slutskaya, E.; Stepanov, A.; Argentova-Stevens, A.; Shirshin, E.; Tsoraev, G.; Klementiev, K.; Slatinskaya, O.; Lukashev, E.; Friedrich, T.; et al.
Abstract The 35-kDa Orange Carotenoid Protein (OCP) is responsible for photoprotection in cyanobacteria. It acts as a light intensity sensor and efficient quencher of phycobilisome excitation. Photoactivation triggers large-scale conformational rearrangements to convert OCP from the orange OCPO state to the red active signaling state, OCPR, as demonstrated by various structural methods. Such rearrangements imply a complete, yet reversible separation of structural domains and translocation of the carotenoid. Recently, dynamic crystallography of OCPO suggested the existence of photocycle intermediates with small-scale rearrangements that may trigger further transitions. In this study, we took advantage of single 7 ns laser pulses to study carotenoid absorption transients in OCP on the time-scale from 100 ns to 10 s, which allowed us to detect a red intermediate state preceding the red signaling state, OCPR . In addition, time-resolved fluorescence spectroscopy and the assignment of carotenoid-induced quenching of different tryptophan residues derived thereof revealed a novel orange intermediate state, which appears during the relaxation of photoactivated OCPR to OCPO . Our results show asynchronous changes between the carotenoid- and protein-associated kinetic components in a refined mechanistic model of the OCP photocycle, but also introduce new kinetic signatures for future studies of OCP photoactivity and photoprotection.